Climate change in dry lands of Central Asia: from assessment methods to adaptation strategies - Glazirina, M.; Yuldashev, Tulkun; Sommer, Rolf (2012)
Global climate change is one of the main issues discussed at various international and intergovernmental meetings and consultations. Since the mid-1990s, the issue went beyond the scientific papers and discussions and became the subject of discussions among policy makers. Key issues of climate change impact on the environment, economic development, wellbeing, health and safety of the population, often discussed in various scientific and political forums, and many of them have been set up as priority for coordinated actions. In 1990, the First Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) has been published, which presented the first systematic scientific views on climate forecasts, assessment of the impact of global warming and measures to adapt to the upcoming changes. The Fourth Assessment Report of the WMO/UNEP Intergovernmental Panel on Climate Change (lPCC) released in 2007, suggested several adaptation strategies to deal with projected climatic changes which include, changing crop varieties; enhancing more efficient water use; appropriate scheduling of cropping activities; adoption of more effective pest, disease and weed management practices and insurance; and making better use of seasonal climate forecasts to reduce production risks. A comprehensive and integrated approach to planning and implementing the climate change adaptation strategies across the wide range of agroecosystems in different countries in CAC could help both the planners and the local communities to deal effectively with the projected impacts and also contribute to mitigation of climate change.